PENGEMBANGAN DIORAMA AIR ENERGI LISTRIK (DIOSTRIK) BERBASIS STEM PADA MATERI SIKLUS AIR DALAM MENINGKATKAN SELF REGULATED DAN LITERASI SAINS SISWA KELAS V SEKOLAH DASAR - Pratama, Muchamad Rizal Ilham; Fatih, Mohammad; Oktaviani, Ragil Tri (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to develop a STEM-based learning media called Diostrik (Diorama of Water and Electric Energy) for the fifth-grade science topic on the water cycle at SDN Modangan 5, Blitar Regency. The research employed a Research and Development (R&D) method adapted from Borg and Gall’s model, which originally consists of ten stages, but was modified into seven due to research limitations. The results indicate that Diostrik is feasible for use in IPAS (Science and Social Studies) learning, as validated by material experts, media experts, and teacher feedback. Moreover, the media effectively improved students’ understanding of the water cycle, particularly their self-regulated learning and scientific literacy skills. This improvement was supported by statistical analysis using a paired t-test, which showed a significance value of 0.000 (< 0.05), indicating a significant difference between pre-test and post-test results. Therefore, the Diostrik STEM-based learning media is proven to enhance students’ conceptual understanding, self-regulation, and scientific literacy in learning the water cycle concept.